American foreign policy : the dynamics of choice in the 21st century - Jentleson, Bruce W., 1951- (New York ; London : W.W. Norton & Company, 2014)
"[This] text addresses the most pressing foreign policy questions of this global era: How should the United States wield its power, pursue peace, promote prosperity and be true to its principles? [The book] helps students approach these issues by applying a consistent critical framework throughout ... emphasizing both the strategic and the political aspects of foreign policy decision making."--Back cover.
Part I: The context of U.S. foreign policy : theory and history -- The strategic context : foreign policy strategy and the essence of choice -- The domestic context : the three branches and the process of choice -- The domestic context : interest groups, media, and public opinion -- The historical context : great debates in American foreign policy, 1789-1945 -- The Cold War context : origins and first stages -- The Cold War context : lessons and legacies -- Readings for Part I -- Part II: American foreign policy in the twenty-first century : choices and challenges -- Grand strategy for a new era : (I) power and peace -- Grand strategy for a new era : (II) prosperity and principles -- Post-Cold War foreign policy politics : politics beyond the water's edge -- Asia's rising strategic importance : relations with China and in the Asia-Pacific Region -- War, peace, terrorism, democracy : old and new challenges in the Middle East -- Old friends, old enemy: 21st century relations with Europe and Russia -- The Americas : relations with Latin America and Canada -- Africa : persisting old issues, pressing newer ones -- Readings for Part II.
Includes bibliographical references (pages A-1-A-3 and index.
Keywords: Since 1989; 2000-talet; Diplomatic relations; United States -- Foreign relations -- 21st century